Metal stents: a bridge to surgery in hilar cholangiocarcinoma. Issue 5 (16th October 2012) - Grünhagen, Dirk J.; Dunne, Declan F.J.; Sturgess, Richard P.; Stern, Nick; Hood, Stephen; Fenwick, Stephen W.; Poston, Graeme J.; Malik, Hassan Z.
Abstract Background Obstructive jaundice in patients with hilar cholangiocarcinoma is a known risk factor for hepatic failure after liver resection. Plastic stents are most widely used for preoperative drainage. However, plastic stents are known to have limited patency time and therefore, in palliative settings, the self‐expanding metal stent (SEMS) is used. This type of stent has been shown to be superior because it allows for rapid biliary decompression and a reduced complication rate after insertion. This study explores the use of the SEMS for biliary decompression in patients with operable hilar cholangiocarcinoma. Methods A retrospective evaluation of a prospectively maintained database at a tertiary hepatobiliary referral centre was carried out. All patients with resectable cholangiocarcinoma were recorded. Results Of 260 patients referred to this unit with cholangiocarcinoma between January 2008 and April 2012, 50 patients presented with operable cholangiocarcinoma and 27 of these had obstructive jaundice requiring stenting. Ten patients were initially treated with SEMSs; no stent failure occurred in these patients. Seventeen patients initially received plastic stents, seven of which failed in the interval between stent placement and laparotomy. These stents were replaced by SEMSs in four patients and by plastic stents in three patients. Median time to laparotomy was 45 days and 68 days in patients with SEMSs and plastic stents, respectively. Conclusions Self‐expanding metal stents provide adequate and rapid biliary drainage in patients with obstruction caused by hilar cholangiocarcinoma. No re‐interventions were required. This probably reflects the relatively short interval between stent placement and laparotomy.